Protective effect of hyperoside against renal ischemia-reperfusion injury via modulating mitochondrial fission, oxidative stress, and apoptosis. (3rd July 2019) - Wu, Lin; Li, Qing; Liu, Simeng; An, Xiaofei; Huang, Zhimin; Zhang, Bo; Yuan, Yanggang; Xing, Changying
Abstract: Ischemia/reperfusion (IR) is a common cause of acute kidney injury (AKI). However, effective therapies for IR-induced AKI are lacking. Hyperoside is an active constituent in the flowers of Abelmoschus manihot (L.) Medic, which is a traditional Chinese herbal medicine for the treatment of various ischemic brain and heart diseases. Our previous study demonstrated that hyperoside inhibited adriamycin induced podocyte injury both in vivo and in vitro . The aim of this study is to investigate the effect of hyperoside in IR-induced AKI. In mice, pretreatment of hyperoside could markedly attenuate IR-induced AKI, tubular cell apoptosis, and oxidative stress in the kidneys. Meanwhile, we found hyperoside inhibited IR-induced mitochondrial fission by suppressing OMA1 mediated proteolysis of optic atrophy 1 (OPA1). Consistently, in human proximal tubular epithelial cells, hyperoside might inhibit CoCl2 -induced mitochondrial fission, oxidative stress, and apoptosis by regulating OMA1-OPA1 axis. Taken together, our results support the idea that OMA1-OPA1 mediated mitochondrial fission can be used for the prevention of AKI. Hyperoside might have novel therapeutic potential in the treatment of AKI.